Mass Spectrometry - Aliofkhazraei, Mahmood (IntechOpen, 2017)
Mass spectrometry is an analytical technique that can be used for the structural characterization and quantification of a wide range of molecules. The technique is extensively used by chemists for the analysis of small and volatile organic compounds. Mass spectrometry has long been an important technique for the identification of materials ranging from pure compounds to complex mixtures. Mass spectrometry can be used to determine molecular weight of compounds or using different ionization conditions, can provide more structural details through the analysis of fragmentation patterns. This level of detail can be attained for pure compounds and some mixtures. Mass spectrometry can also be combined with separation techniques such as gas chromatography or liquid chromatography to allow more complex mixtures to be examined. These hyphenated techniques provide a range of options for the characterization of complex materials.